On the effects of the fuel injection phase on heat release and soot formation in counterflow flames - Lopez, Luis; Giusti, Andrea; Gutheil, Eva; Olguin, Hernan (Energy, 2022)
Total rates of heat release, ω̇T,tot, and soot emission, ω̇Ys,tot, are studied in ethanol-N2/air and n-butanol-N2/air counterflow flames. A gas flame is first established as a base case and fractions of the gaseous fuel are then replaced by droplets and nitrogen, keeping the total fuel mass flux constant. Several values of the liquid to total fuel mass ratio, φl, are employed, covering the entire range from a gas flame to a spray flame (0 ≤ φl ≤ 1). Different initial droplet radii, R0, are considered, as well as both low and close to extinction strain rates. Results show qualitative similarities for both fuels, even though quantitative differences are observed. In general, ethanol flames release more heat and less soot than n-butanol flames. For low strain rates, φl = 1 leads to lower soot emissions than for the reference gas flame, independently of R0. Also, ω̇T,tot is higher for R0 = 25 and 40 μm. Close to extinction, increasing φl notoriously improved ω̇T,tot without considerably raising ω̇Ys,tot for R0 = 25 μm. Also, for R0 = 40 μm, there are some particular values of φl for which similar situations occur. These results show that the fuel injection phase plays an important role in optimizing combustion processes.